Impact of Innate Immunity, Endothelial Damage, and Metabolic Biomarkers on COVID-19 Severity and Mortality. (20th August 2022) - Rocco, Joseph M; Laghetti, Paola; Di Stefano, Mariantonietta; Sereti, Irini; Ortega-Villa, Ana; Wang, Jing; Rupert, Adam; Chironna, Maria; Ye, Lara; Liu, Xiangdong; Anderson, Megan V; Burbelo, Peter B; et al.
Abstract: In this study, abnormal levels of myeloid activation, endothelial damage, and innate immune markers were associated with severe coronavirus disease 2019 (COVID-19), while higher levels of metabolic biomarkers (irisin, leptin) demonstrated a protective effect. These data support a model for COVID-19 immunopathogenesis linking robust inflammation and endothelial damage in metabolically predisposed individuals.